User's adherence to hypertensive drug therapy - Zélia Maria de Sousa Araújo Santos; Helder de Pádua Lima; Flávia Braga de Oliveira; Jamilly Silva Vieira; Natasha Marques Frota; Jennara Candido do Nascimento (Rev Rene)
The low treatment adherence is one of the major factors for the lack of blood pressure control and risk for cardiovascular diseases. We aimed to analyze the hypertensive user's adherence to drug therapy. A descriptive study carried out with 400 hypertensive users, from May to August 2010, through interviews. Most interviewees were female (67.2%), aged over 60 (54.3%) and with brown skin (57.4%). 326 (81.5%) users were making regular use of medicine with a predominance of those with over 10 years of diagnosis (33.5%), those with up to 5 years of treatment (31.0%), and those who received the complete medication provided by SUS (39.2%). The knowledge on the types of antihypertensive drugs and the daily frequency of medication prevailed regardless the regularity of medication, the same happened regarding the lack of knowledge on side effects, to the discomforts caused and the complexity of drug therapy. We concluded that the treatment adherence prevailed in most users.